2021
DOI: 10.1111/mmi.14794
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of isoprenoid lipids in Methylobacterium extorquens PA1

Abstract: Microorganisms can withstand a diversity of environmental stresses ranging from extreme temperatures to the immune defenses of multicellular organisms. The cell surface membrane serves as a first line of defense against environmental perturbations and the membrane's lipid composition is critical for stress resistance. On the one hand, the membrane must be robust enough to withstand chemical and physical challenges. On the other hand, the membrane must be fluid enough to support bioactivity. In eukaryotic organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…To assess relative changes in permeability we employed an assay based on the hydrolysis of FDA to fluorescein after it diffuses into the cell (47,48). Three biological replicates of each strain were grown until till early exponential (OD 600 = 0.5).…”
Section: Induction Conditions and Reporter Activity Measurementsmentioning
confidence: 99%
“…To assess relative changes in permeability we employed an assay based on the hydrolysis of FDA to fluorescein after it diffuses into the cell (47,48). Three biological replicates of each strain were grown until till early exponential (OD 600 = 0.5).…”
Section: Induction Conditions and Reporter Activity Measurementsmentioning
confidence: 99%
“…The Δ shc mutant colonies displayed an intense red color ( Fig. 2 A ), indicating that the accumulated squalene (or its precursors) is re-directed toward carotenoid production, as observed in M. extorquens ( 7 , 13 ). Indeed, we confirmed squalene production via HpnCDE using the Δ crtN -Δ shc strain, since squalene is the precursor of hopanoids ( Fig.…”
Section: Resultsmentioning
confidence: 82%
“…4C), we observe that most of these co-occurrences have non-overlapping patterns of distribution, e.g., in the Halobacterota phylum, Halobacteria and Methanonatronarchaeia classes have C40 and C30 pathways, respectively, or Methylococcales which switched squalene and carotenoid synthesis to Sqs and C30 pathways or in Bacteroidetes presenting both C40 pathways. Conversely, other cases have both complete C30 and C40 pathways, such as some α-proteobacterial orders, although in M. extorquens only the C30 pathway is functional in normal conditions (7). Other cases, such as some Firmicutes species, present a mix of one complete (C30) and other partial (CrtH) pathway, showing the coexistence of enzymes from different pathways in the same organism.…”
Section: Pervasive Lgt Of Carotenoid Biosynthetic Pathways and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a simple but distinctive lipidome has been proposed to serve complementary roles in OM adaptation. 26 In this frame, a significant part of M. extorquens lipidome is occupied by the lipid A portion of the LOS (Figure 4), which is the main constituent of the OM, constantly exposed to highly mutable environmental stimuli and dangers. From a strict LPS chemistry point of view, here, we showed that M. extorquens lipid A has a non-phosphorylated tetraacylated sugar skeleton, carrying 18:0(3-OH) and 14:0(3-OH) as primary acyl chains on the distal GlcN, and a secondary 26:0(25-OH) [minor 28:0(27-OH)], in turn acylated by a novel 3-O-acetyl-butyrate residue, which to the best of our knowledge has never been found in lipid A.…”
Section: ■ Discussionmentioning
confidence: 99%